2018
DOI: 10.3892/ol.2018.8376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways in meningioma by bioinformatics analysis

Abstract: Meningioma is the most frequently occurring type of brain tumor. The present study aimed to conduct a comprehensive bioinformatics analysis of key genes and relevant pathways involved in meningioma, and acquire further insight into the underlying molecular mechanisms. Initially, differentially expressed genes (DEGs) in 47 meningioma samples as compared with 4 normal meninges were identified. Subsequently, these DEGs were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…MYC proteins drive an increased cellular proliferation and facilitate multiple aspects of tumor initiation and progression, thereby controlling all hallmarks of cancer [ 38 ]. A previous study has reported that MYC is a hub gene in meningioma, which is consistent with our results [ 39 ]. Another molecule predicted is PTGS2, which encodes the COX-2 enzyme and is expressed in many tumor types [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…MYC proteins drive an increased cellular proliferation and facilitate multiple aspects of tumor initiation and progression, thereby controlling all hallmarks of cancer [ 38 ]. A previous study has reported that MYC is a hub gene in meningioma, which is consistent with our results [ 39 ]. Another molecule predicted is PTGS2, which encodes the COX-2 enzyme and is expressed in many tumor types [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…By integrating results from Upstream regulator and Downstream effects tools, we can create hypotheses that explain what is going on upstream to the experimentally measured gene changes that are linked to a phenotype or other functional outcomes. For instance, regulator effects analysis (Fig 9) shows all predicted upstream genes for hippocampal TBI-induced gene changes at 24 hr are key hub genes that have essential roles in cell function and disease [5557]. Moreover, many of the genes we find significantly altered by TBI, such as Atf3 [58], are also hub genes and/or transcriptional regulators of essential cell functions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, with the continuous development of bioinformatics and molecular biology, microarray technology has been widely used for exploring the molecular mechanisms of various diseases (911). In previous decades, analysis of the expression profiles of gene microarrays was used to identify several key genes and diagnostic biomarkers of IBDs, including several differentially expressed genes (DEGs) involved in different pathways, biological processes or molecular functions (12,13).…”
Section: Introductionmentioning
confidence: 99%